Characterization and application of dolomite rock in Perlis - Mohd Nazry, Salleh; Farizul Hafiz, Kasim; Khairul Niza,r Ismail; Che Mohd Ruzaidi, Ghazali; Saiful Azhar, Saad; Suhardy, Daud (Universiti Teknologi Malaysia (UTM), 2008)
Organized by Universiti Teknologi Malaysia (UTM), 24th - 25th July 2006 at Putrajaya, Malaysia.